Research trends of carbon dioxide capture using ionic liquids and aqueous amine-lonic liquids mixtures / Siti Nabihah Jamaludin and Ruzitah Mohd Salleh - Jamaludin, Siti Nabihah; Mohd Salleh, Ruzitah (Penerbit UiTM (UiTM Press), 2016)
Anthropogenic C0₂ emissions has led to global climate change and widely contributed to global warming since its concentration has been increasing over time. It has attracted vast attention worldwide. Currently, the different C0₂ capture technologies available include absorption, solid adsorption and membrane separation. Chemical absorption technology is regarded as the most mature technology and is commercially used in the industry. However, the key challenge is to find the most efficient solvent in capturing C0₂. This paper reviews several types of C0₂ capture technologies and the various factors influencing the C0₂ absorption process, resulting in the development of a novel solvent for C0₂ capture.